Compliance Programs as a Mechanism to Fight Corruption: Special Reference to Self-Regulation of Companies - Astudillo Meza, Guillermo (2015)
This article analyzes the influence self-regulation has had in the recent years as a law instrument that helps monitor corporate organizations, as well as its consequences in the fight against public corruption through corporate compliance programs.